Financial development and performance of palm oil industry in Malaysia - Syajarul Imna Mohd Amin; Aisyah Abdul-Rahman; Hawati Janor; Abdullah Khairi Mohd Asri; Darmawati Muchtar (Economic Journal of Emerging Markets, 2019)
The finance-growth nexus is gaining credence among researchers. Growing research interest in developing evidences for different economic sectors has ignited this study to examine the topic in agricultural sector for Malaysia. The analysis focuses on palm oil industry using data for the period 1981 to 2017 using the Autoregressive Distributed Lagged (ARDL-bounds) approach. Financial development measures financial depth, accessibility, efficiency, and stability. Other variables include production factors such as land, labour and capital. Findings/Originality: The findings show that the depth of financial market has positive impact on palm oil industry performance both in the short run and long run, though the depth of the financial institutions only take effect in the long run. Meanwhile the financial accessibility, efficiency and stability have no significant effect on the productivity of the industry. It implies that the equity market development is more relevant to affect the palm oil industry compared to credit market development.